A Novel Mouse Model of Idiopathic Nephrotic Syndrome Induced by Immunization with the Podocyte Protein Crb2. Issue 11 (November 2022) - Hada, Ichiro; Shimizu, Akira; Takematsu, Hiromu; Nishibori, Yukino; Kimura, Toru; Fukutomi, Toshiyuki; Kudo, Akihiko; Ito-Nitta, Noriko; Kiuchi, Zentaro; Patrakka, Jaakko; Mikami, Naoaki; Leclerc, Simon; et al.
Significance Statement: The cause of podocyte injury in idiopathic nephrotic syndrome (INS) remains unknown. Although clinical evidence points to an autoimmune origin, currently available animal models are not mediated by autoimmunity, limiting further research on the mechanisms leading to INS. We developed a mouse model mimicking human INS, induced by immunization with the podocyte foot process protein Crb2. Mice developed anti-Crb2 autoantibodies and heavy proteinuria, mimicking pathological features of minimal change disease or FSGS in humans. The results indicate that autoantibodies against podocyte proteins can injure the cells, causing nephrotic syndrome in mice. Crb2 immunization could be a useful model to study the full immune pathogenesis of human INS. Visual Abstract: Abstract : Background: The cause of podocyte injury in idiopathic nephrotic syndrome (INS) remains unknown. Although recent evidence points to the role of B cells and autoimmunity, the lack of animal models mediated by autoimmunity limits further research. We aimed to establish a mouse model mimicking human INS by immunizing mice with Crb2, a transmembrane protein expressed at the podocyte foot process. Methods: C3H/HeN mice were immunized with the recombinant extracellular domain of mouse Crb2. Serum anti-Crb2 antibody, urine protein-to-creatinine ratio, and kidney histology were studied. For signaling studies, a Crb2-expressing mouse podocyte line was incubated with anti-Crb2 antibody. Results: Serum anti-Crb2 autoantibodies and significant proteinuria were detected 4 weeks after the first immunization. The proteinuria reached nephrotic range at 9–13 weeks and persisted up to 29 weeks. Initial kidney histology resembled minimal change disease in humans, and immunofluorescence staining showed delicate punctate IgG staining in the glomerulus, which colocalized with Crb2 at the podocyte foot process. A subset of mice developed features resembling FSGS after 18 weeks. In glomeruli of immunized mice and in Crb2-expressing podocytes incubated with anti-Crb2 antibody, phosphorylation of ezrin, which connects Crb2 to the cytoskeleton, increased, accompanied by altered Crb2 localization and actin distribution. Conclusion: The results highlight the causative role of anti-Crb2 autoantibody in podocyte injury in mice. Crb2 immunization could be a useful model to study the immunologic pathogenesis of human INS, and may support the role of autoimmunity against podocyte proteins in INS.